Meningkatkan Hasil Belajar SKI Siswa Kelas XI IPA dengan Menggunakan Metode Mind Mapping di MAN 3 Solok - Lestari, Atika Putri; Charles, Charles; Ersisri, Ersisri (Yayasan Lembaga Studi Makwa, 2024)
This study examines the implementation of the Mind Mapping method in the teaching of Islamic Cultural History (SKI) at MAN 3 Solok as an effort to improve the learning outcomes of 11th-grade students. Low student participation and difficulties in understanding the material necessitate innovative strategies to create a more engaging and effective learning environment. To address these challenges, this study employs a qualitative approach using Classroom Action Research (CAR) methodology. The research follows several stages, including initial observations, lesson planning, the implementation of the Mind Mapping method, and an evaluation of its effectiveness. Data collection techniques involve classroom activity observations, documentation of student progress, and interviews with both students and teachers to gain a comprehensive understanding of the method’s impact. The findings indicate a significant improvement in students’ learning outcomes after implementing the Mind Mapping method. In the pre-cycle stage, the average student score was only 44.94, with a mastery level of 8%. After the first cycle, the average score increased to 70.04, with a mastery level of 42%. In the second cycle, the results improved further, with an average score of 85.95 and a mastery level reaching 86%. These findings demonstrate that the Mind Mapping method effectively enhances students' comprehension and engagement in SKI learning. This study contributes to the field of education by providing empirical evidence of the effectiveness of Mind Mapping in Islamic studies, encouraging educators to adopt student-centered learning methods to enhance understanding and critical thinking skills. Additionally, this research has practical implications for curriculum development, particularly in integrating visual and interactive techniques to promote active learning in history education.